Post-COVID Reflections from a General Dental Practice Perspective - Afolabi Ogunderu; O. Ogunderu (Nigerian Dental Association, 2023)
OVID-19 took the world by a storm, private dental practitioners inclusive.  This perspective paper briefly highlights the challenges faced by private dental practitioners in Nigeria while the pandemic lasted. The author highlighted the response and guidelines issued by the ministry of health and how private dental practice adjusted to the new realities. It concluded with the recommendation that despite the end of COVID-19 as an emergency, infection control practices must still be upheld, post-COVID and at all times.